HIV prevalence and trends from data in Zimbabwe, 1997–2004. (30th March 2006) - Mahomva, A; Greby, S; Dube, S; Mugurungi, O; Hargrove, J; Rosen, D; Dehne, K-L; Gregson, S; St Louis, M; Hader, S
Abstract : Background: This paper brings together data from a variety of reports to provide a basis for assessing future steps for responding to and monitoring the HIV epidemic in Zimbabwe. Method: Data reported from four antenatal clinic (ANC) surveys conducted between 2000 and 2004, two small local studies in Zimbabwe conducted from 1997 through 2003, four general population surveys from 1999 through 2003, and service statistics covering 1990 through 2004 were used to describe recent trends in HIV prevalence and incidence, behaviour change, and programme provision. Results: HIV prevalence among pregnant women attending ANCs declined substantially from 32.1% in 2000 to 23.9% in 2004. The local studies confirmed the decline in prevalence. However, prevalence continued to be high. Sexual behaviour data from surveys suggests a reduction in sexual experience before age 15 years among both males and females age 15–19 years, and in the proportions of males and females aged 15–29 years reporting non-regular sexual partners in the past 12 months. Reported condom use with non-regular partners has been high since 1999. Condom distribution and HIV counseling and testing increased from 2000 to 2004. Discussion: On the basis of examination of data from a variety of sources, the recent decrease in HIV prevalence may be related to recent reductions in early-age sexual activity and non-regular sexual partnerships and increases in condom use. Comparison of data from sentinel surveillance systems, population based serosurveys, local studies, and service statistics provide increased confidence that a decline in HIV prevalence in Zimbabwe is actually happening in the population.